Women's Participation in Political Parties and Simultaneous Elections - Djou, Ana Maria Gadi; Quintarti, M.A. Liza (Law Research Review Quarterly, 2018)
Women's representation on the political stage still leaves serious problems, in fact, Law Number 8 of 2012 concerning General Elections of Members of the DPR, DPD and DPRD confirms that the representation of women is at least 30 percent. One of the classic reasons that became the scapegoat of the political backwardness of women is a matter of patriarchal culture, namely women are considered more suited to take care of the domestic (private) while the male public. Political parties' alignments towards gender equality are still half-hearted. Every ahead of the election almost all political parties try to adopt a gender perspective (gender perspective). However, this intention does not appear to be truly sincere because the perspective of gender perspective only wants to maintain the existence of the party so that it is in accordance with the requirements of the Act. In fact, the representation of women is crucial given the decisions in the executive and legislative branches covering all aspects of national and state life. This study aims to show that as an important pillar of democracy, it is time for political parties to take part in the success of the agenda for women's representation. The results of this study indicate that political parties must have a real commitment to realize women's representation by being proven in writing into the party platform. Parties can use wing organizations engaged in the field of women as a source of cadres for political parties.